COLLECTION STORAGE ANALYSIS AS A PREVENTIVE STEP IN PRESERVATION ACTIVITIES AT MANDALA WANGSIT SILIWANGI MUSEUM - Pratama, Anandita Fitriani (Jurnal Literasi Perpustakaan dan Informasi: Jurnal Penelitian Kajian Perpustakaan dan Informasi, 2023)
This study examines the implementation of preventive preservation activities in the aspect of collection storage at the Mandala Wangsit Siliwangi Museum, as well as the obstacles faced by the museum during preservation activities. The research method used is descriptive qualitative analysis with data sources obtained from observations, interviews with museum staff, and literature studies. The results showed that preventive preservation, especially in the storage of collections at the Mandala Wangsit Siliwangi Museum, was carried out by placing each collection in a glass display case and using a railing stand for large collections, periodic cleaning, and fumigation to prevent pests from damaging the collectibles. Obstacles that can hinder the museum in carrying out preservation activities are the lack of support and supply of funds from the local government, as well as the lack of human resources.